Cancer bio-repository - Shima Fakher (Shiraz University of Medical Sciences, 2019)
Background: Cancer research is highly dependent of large amount of data and high quality samples which can be provided by networks to enable large-scale multi-center research projects. Biologic materials, such as blood, tissue samples, DNA, body fluids and the related data obtained in cohorts and clinical trials are valuable sources for research which should be managed by policies and standard operating procedures as biorepositories or biobanks. Methods and evidence acquisition: The authors investigated and summarized pubmed database articles using biobanks and describing the policies. Conclusion: biobanking as a young discipline in different countries needs new technologies, standards and harmonization. In this review article, we have an overview on biorepository, cancer biobanking and the emerging registry in Iran. Background: Cancer research is highly dependent of large amount of data and high quality samples which can be provided by networks to enable large-scale multi-center research projects. Biologic materials, such as blood, tissue samples, DNA, body fluids and the related data obtained in cohorts and clinical trials are valuable sources for research which should be managed by policies and standard operating procedures as biorepositories or biobanks. Methods and evidence acquisition: The authors investigated and summarized pubmed database articles using biobanks and describing the policies. Conclusion: biobanking as a young discipline in different countries needs new technologies, standards and harmonization. In this review article, we have an overview on biorepository, cancer biobanking and the emerging registry in Iran.